2017
DOI: 10.1111/sms.12830
|View full text |Cite
|
Sign up to set email alerts
|

Excess of exercise increases the risk of atrial fibrillation

Abstract: An interesting and still not well-understood example for old medical wisdom "Sola dosis facit venenum" is the increased prevalence of atrial fibrillation (AF) in athletes. Numerous studies have shown a fourfold to eightfold increased risk of AF in athletes compared to the normal population. Analysis of the existing data suggests a dose-dependent effect of exercise. Moderate exercise seems to have a protective effect and decreases the risk of AF, whereas excessive exercise seems to increase the risk of AF. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Some epidemiological studies reported an increased risk of disease and/or mortality at the highest exercise volumes [ 4 , 9 ••, 10 ], suggesting that health benefits of an active lifestyle may plateau or even decline in extreme exercisers [ 11 ]. Cross-sectional studies have reported that the most active veteran endurance runners have an increased risk for myocardial fibrosis [ 12 , 13 ], coronary artery calcification [ 14 •], and atrial fibrillation [ 15 ]. These observations imply that high volumes of chronic endurance exercise training may be detrimental for the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies reported an increased risk of disease and/or mortality at the highest exercise volumes [ 4 , 9 ••, 10 ], suggesting that health benefits of an active lifestyle may plateau or even decline in extreme exercisers [ 11 ]. Cross-sectional studies have reported that the most active veteran endurance runners have an increased risk for myocardial fibrosis [ 12 , 13 ], coronary artery calcification [ 14 •], and atrial fibrillation [ 15 ]. These observations imply that high volumes of chronic endurance exercise training may be detrimental for the heart.…”
Section: Introductionmentioning
confidence: 99%
“…The American Heart Association and American College of Cardiology both recommend the following tests be done for any athlete with AF: performance-enhancing/illicit drug use questioning, thyroid function testing, electrocardiography, and echocardiography (Class I recommendations) [ 7 ]. It has been suggested that moderate levels of exercise will have a protective effect and may even decrease the incidence of AF, whereas excessive endurance exercise heightens the risk of AF [ 9 ]. As for anticoagulation with exercise-related AF, recommendations are based on the presence of known risk factors for thromboembolism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early ablation may be beneficial for athletes with impaired physical performance, especially if they want to remain competitive [5]. For some athletes whose performance was impaired by AF, multiple pulmonary vein ablations have proven successful in restoring full competitive function and allowed these athletes to participate in their activities again [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that athletes with paroxysmal atrial fibrillation (AF) or paroxysmal atrial flutter (AFL) (which may be particularly dangerous for athletes) should use HRMs as a device to monitor and control HR. Frequent attacks of AF or AFL occur in athletes, active people, and patients above a certain basic HR . In such cases, the HRM should be the primary auxiliary tool used to control HR in both symptomatic and asymptomatic persons.…”
Section: Discussionmentioning
confidence: 99%